PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SHOLAT JENAZAH DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI PADA KELAS XI TKJ DI SMK NEGERI 1 KUANTAN MUDIK - Nade Ratul Anggina (Universitas Islam Kuantan Singingi, 2020)
Method [is] the way of important in study so that the student feel interested to follow taught Iesson. Method Demonstrate [is] a[n way of presentation in course of learning to teach with show [of] about way of [doing/conducting] something joined with clarification visually from clear process so that will be more easy to in submitting Iesson items. SMK of Country 1 Pestle Go upstream specially class of XI TKJ [of] [at] items of sholat of corpse found [by] some symptom that is : result learn student which still lower, student less be active in course of study, student only look on teacher of moment of study [of] because method used lose looks, and also the inexistence applied [by] practice of procedures of sholat corpse. One of method of study which can be applied to increase result of learning the student [is] method Demonstrate. Type Penelltian [is] Class Action Research Technique [of] data collecting used [by] [is] observation, tes, interview, and documentation. Result of research indicate that happened [by] improvement [of] result of learning student [of] [at] items sholat corpse in religion islam ethic kindness and education subject [in] SMKN 1 Pestle Go upstream. This Matter [is] proved from visible Cycle Pre only 50% the student which is result of learning nya categorized complete, cycle I mount to become 80%, and cycle II also experience of very improvement gratify that is 100% student which is result of learning nya have been categorized complete ( above KKM).